2010
DOI: 10.1097/mat.0b013e3181e5de0a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of von Willebrand Factor Profiles in Pulsatile and Continuous Left Ventricular Assist Device Recipients

Abstract: A higher rate of nonsurgical bleeding has been observed in nonpulsatile left ventricular assist device (LVAD) recipients. von Willebrand factor (vWF) profiles were compared for nonpulsatile and pulsatile LVAD recipients to explore mechanisms that may contribute to the development of postimplant nonsurgical bleeding. The nonpulsatile mechanism may impair vWF function by creating a deficiency in vWF high molecular weight multimers (HMWMs), essential for hemostasis. High molecular weight multimer deficiency shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…In addition, bleeding events occurred even in the absence of supratherapeutic anticoagulation, 30,32 a fact also seen in our study where 82% of the patients with bleeding had an INR within the desired therapeutic range. Other factors have been implicated in the increased incidence of bleeding in CF-LVADs, including the development of acquired von Willebrand syndrome, 14,16,17,33,34 impairment in platelet aggregation, 15 and the lack of pulsatility. The potential role of the first 2 factors in the bleeding diathesis observed in patients with CF-LVADs has been investigated; however, the role of pulsatility in this setting is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bleeding events occurred even in the absence of supratherapeutic anticoagulation, 30,32 a fact also seen in our study where 82% of the patients with bleeding had an INR within the desired therapeutic range. Other factors have been implicated in the increased incidence of bleeding in CF-LVADs, including the development of acquired von Willebrand syndrome, 14,16,17,33,34 impairment in platelet aggregation, 15 and the lack of pulsatility. The potential role of the first 2 factors in the bleeding diathesis observed in patients with CF-LVADs has been investigated; however, the role of pulsatility in this setting is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…4 We previously reported a universal loss of the HMWM in continuous-flow LVAD recipients. 5 This abnormality may be associated with an increased bleeding risk during the peri-operative and post-operative device support period. Bleeding complications, when present, often require a modification in anticoagulation strategy for some patients.…”
mentioning
confidence: 99%
“…As the shear stress rate increases, the molecule is prone to unfolding, resulting in greater cleavage rates and smaller vWF multimers. 27 Multiple studies 16,17,28 have shown that most patients who undergo implantation with an axial-flow LVAD will develop some degree of acquired von Willebrand disease. In a retrospective review 16 of 79 patients with a HeartMate II LVAD, all patients had decreased or absent HMW vWF multimers that normalized after heart transplantation.…”
Section: Acquired Von Willebrand Disease With Axial-flow Lvadsmentioning
confidence: 99%